1989
DOI: 10.1149/1.2096778
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer Process at Illuminated Semiconductor/Electrolyte Junctions Modified by Electrodeposition of Microscopic Metal Grain

Abstract: Layers made of microscopic Pt grains, optically transparent, with various morphologies are deposited on n-GaAs by electrocrystallization. It is shown that the modified GaAs photoanode is long-term stabilized under illumination in aqueous electrolytes provided that the film presents some required structural properties, e.g., size and density of Pt nuclei. In fact, correlations between the film morphology [studied by transmission electron microscopy (TEM)] and the stabilization of the modified electrode [studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…According to previous experimental investigations, layers of various metal such as Ru, Pt, Ag or Pb electrodeposited on GaAs single crystal are made of tiny independant crystallites which don't have any epitaxial relation with the substrate [6]. In the present study, the formation of continuous epitaxial nickel films is certainly due to the strong reactivity between nickel and gallium arsenide.…”
mentioning
confidence: 67%
“…According to previous experimental investigations, layers of various metal such as Ru, Pt, Ag or Pb electrodeposited on GaAs single crystal are made of tiny independant crystallites which don't have any epitaxial relation with the substrate [6]. In the present study, the formation of continuous epitaxial nickel films is certainly due to the strong reactivity between nickel and gallium arsenide.…”
mentioning
confidence: 67%
“…In photocatalysis, metal islands on p-type semiconductors [30][31][32][33][34][35][36][37][38][39][40][41] have been shown to catalyse charge transfer processes such as the reduction of water. In this case the metal islands can be viewed as electronic surface states.…”
Section: Case 2: Reduction Of Metal Ions Via Surface Statesmentioning
confidence: 99%
“…For deposition of metals onto semiconductors, the critical nucleus size has been reported to be close to unity, implying a barrierless nucleation process. However, the determination of |η| in equations (39) and (41) for semiconductor surfaces is not straightforward. The implications of this will be discussed in section 6.3.4.…”
Section: The Potential Dependence Of Nucleation For 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, simple recombination of the e-h pairs is the major hindrance leading to a low quantum yield (<5%). Some recent research confirmed that a number of metal islands (Heller and Miller, 1980;Allongue et al, 1989; or metal oxides (Gopidas et al, 1990;Bedja et al, 1994;Anderson and Bard, 1995) were introduced into the TiO 2 lattice for accelerating the e-h separation. Alternatively, the thermal hydrogen (H 2 ) treatment of TiO 2 was also found to be capable to prolong the holesÕ lifetime by reducing the number of bulk recombination centers (Harris and Schumacher, 1980;Heller et al, 1987).…”
Section: Introductionmentioning
confidence: 98%